A simple combinatorial treatment for the q-series interpreted by Agarwal - Sharma S.; Rana M. (Utilitas Mathematica, 2020)
A constructive approach is applied to establish the (n+t)-color partition theoretic interpretations of some generalized q-series, which have earlier interpretations in terms of split (n + t)-color partitions. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.